(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify (the effect of the dichotomization strategy on the acquisition of Arabic language grammar among second-year intermediate school female students) The researcher followed the experimental approach and adopted an experimental design with partial control, which is the design of the experimental and control groups with random selection The researcher randomly selected her research sample, which consisted of (72) students, divided into (36) students for the experimental group, and (36) students for the control group, in (Hatin Girls’ Secondary School) affiliated with the General Directorate of Education in Baghdad Governorate/Rusafa II. The researcher rewarded the female students of the two research groups on the following variables: (chronological age calculated in months, academic achievement of fathers and mothers, and Arabic language grades for the previous year). Then the researcher tried to control a number of extraneous variables that previous literature indicated might affect this type of design. Experimental. The same researcher taught the students of the two groups, the experimental group in light of the dichotomization strategy, and the control group in the traditional way during the duration of the experiment, which lasted a semester, which is the second semester of the academic year 2023/2024.The researcher prepared a final test as a tool for her research, consisting of (33) multiple-choice items, which she applied to the experimental and control research groups at the end of the experiment. The researcher used chi-square statistical methods (K2) and the t-test for two independent samples. The research resulted in About the following result:There is a statistically significant difference at the level of (0.05) between the average scores of the female students of the two research groups in acquiring Arabic grammar, and in favor of the experimental grou The researcher made recommendations, including: 1 - Encouraging Arabic language teachers, male and female, at all educational levels to adopt the (dual division) strategy in teaching Arabic grammar. 2 - Conducting training courses for male and female Arabic language teachers in employing and using modern strategies and methods, including the (dual bifurcation) strategy It proposed a number of proposals, including: 1 - Conduct a similar study to research other branches of the Arabic language 2 - Conduct a study similar to research on other academic stages